(untitled) (JURNAL IBU DAN ANAK, 2020)
Abstract Ministry of Health 2017 states that exclusive breastfeeding coverage in Riau in 2017 is 28.57% of the 80% national target. As many as 50% of postpartum mothers who experience breastfeeding problems, such as low breastfeeding on the first to the third day of birth. One way to expedite breastfeeding is by using the oketani massage method. The purpose of this study was to determine the effect of massage on breastfeeding in post partum mothers. This type of research is a quantitative research using a quasi experiment with a post test only design with a control group. This research was conducted from December 2018 to June 2019 at PMB Dince Safrina. The population in this study were all normal post partum mothers from March to May 2019. The sample in this study was 30 post partum mothers taken by purposive sampling. The data collection instrument in this study was the observation sheet that was filled in by the researcher directly through observation, after doing oketani massage for 3 days. Methods of data collection in this study, the intervention group performed oketani massage for 3 days (1 time a day) with a duration of 5-10 minutes and immediately observed it on the third day using observation sheets, and the control group did not do oketani massage. The statistical test used was the Mann Whitney test. The results of this study showed that there was an effect of massage treatment on breastfeeding in post partum mothers (p = 0.003). It is hoped that oketani massage can be applied in PMB Dince Safrina as an alternative to help speed up breastfeeding and prevent problems during breastfeeding in post partum mothers such as flat nipples and breast milk dams.